Spatial variation and determinant factors of alcohol consumption in Ethiopia: Spatial and multilevel analysis of Ethiopian demographic and health survey - Chala Daba; Sisay Abebe Debela; Kassahun Ayele Gasheya; Abel Endawkie; Mesfin Gebrehiwot (PLoS ONE, 2025)
Background Alcohol consumption continues to be a public health problem in Ethiopia. Previous investigations have been conducted on alcohol consumption in Ethiopia; however, these investigations were limited to specific localities, which could not represent the existing alcohol consumption in different parts of Ethiopia. Besides, the spatial variation of alcohol consumption was not well investigated in the previous studies, which could hinder the implementation of effective intervention towards alcohol consumption. Hence, this study aimed to determine the spatial distribution and determinant factors of alcohol consumption in Ethiopia. Methods Secondary data from the 2016 Ethiopian demographic health survey was used in this study. A total of 44,023 weight samples were included using a stratified two-stage cluster sampling technique. The spatial variation of alcohol consumption was analyzed using ArcGIS version 10.7.1. The statistical significance of alcohol consumption clusters were identified using Kuldorff’s SaTScan version 10.2. A multi-level analysis was also conducted to identify factors associated with alcohol consumption using STATA version 14. Results In this study, 33.15% (95%CI: 32.5–33.8) of the study participants consumed alcohol with statistically significant spatial variation across regions of the country. Traditional religion (AOR = 13.7; 95%CI: 2.68–70.3), Regional variations (Amhara region—AOR = 3.56; 95%CI: 1.85–6.8, living in a low proportion of community literacy (AOR = 1.84; 95%CI: 1.1–3.18), cigarette smoking habit (AOR = 15.82; 95%CI: 4.31–58.1), and chewing Khat (AOR = 2.98; 95%CI: 1.22–7.27) were positively linked with alcohol consumption. Hot spot areas of alcohol consumption were found in Tigray, Amhara, and some parts of Oromia regions. The statistical significance of the primary clusters was also observed in Tigray and Amhara regions. Conclusions We found that one-third of Ethiopia’s population is consuming alcohol. Having a cigarette smoking habit, chewing khat, high proportion of community literacy, and traditional religion were associated factors for alcohol consumption. Therefore, the federal government of Ethiopia, and ministry of health, and other concerned bodies should work in collaboration to decrease the proportion of people consuming alcohol.